On the Signature of Black Holes on the Quenched Stellar Mass Function - Antonio J. Porras-Valverde; John C. Forbes (The Astrophysical Journal)
As star-forming galaxies approach or exceed a stellar mass of around 10 ^11 M _⊙ , they are increasingly likely to be quenched in a process generically called mass quenching. Central galaxies, which are quenched via mass rather than environmental quenching, therefore accumulate in a peak around this characteristic mass. While a number of processes may influence the shape of the quenched central stellar mass function, we find that its low-mass slope is strongly affected by the scatter in the mass of black holes at a given stellar mass, with higher scatters in the black hole population yielding shallower slopes. Higher scatters in the black hole mass spread out the stellar mass range over which quenching occurs, leading to shallower slopes. This trend holds across a variety of semianalytic models and cosmological hydrodynamic simulations. A comparison with observations provides indirect evidence for a large scatter in black hole mass $σ ({log}_{10}(M_{{\rm{BH}}})| M_{* })\gtrsim 0.5$ dex, and a joint constraint on active galactic nuclei feedback physics and the coevolution of galaxies and black holes.